2014
DOI: 10.12785/amis/080462
|View full text |Cite
|
Sign up to set email alerts
|

FSFP: Transfer Learning From Long Texts to the Short

Abstract: Abstract:Transfer learning is a method that studies how to identify the useful knowledge and skills in the previous tasks, and uses them to the new tasks or domains. At present, the research on transfer learning mostly focuses on the field of long texts. However, the source data should be given for the transportation from long texts to the short ones, and the priori probability distribution of the data should be given at the same time. In order to solve the problems, the algorithm which is called FSFP (Free So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…One of the current methods to alleviate the above problem is transfer learning, which has been obtained better results in web text data mining [4], document classification [5], [6]. The main idea of transfer learning is to utilize the knowledge from other domain(s) to help learn the current domain.…”
Section: Introductionmentioning
confidence: 99%
“…One of the current methods to alleviate the above problem is transfer learning, which has been obtained better results in web text data mining [4], document classification [5], [6]. The main idea of transfer learning is to utilize the knowledge from other domain(s) to help learn the current domain.…”
Section: Introductionmentioning
confidence: 99%
“…As Pan et al [1] suggested, TL is categorized as Inductive TL [2], [3] (where some labeled data is available in the target domain), Transductive TL [4] (where labeled data is only available in the source domain(s)), and Unsupervised TL [5] (where no labeled data is available in the source(s) and target domains). Inductive TL is the most intuitively appealing because it suggests that some data from the source domain(s) can be taken advantage of with the guidance of a few labeled data in the target domain.…”
Section: Introductionmentioning
confidence: 99%